Big Data Enables E-Government to Implement Sustainable Development - Al Qudah, Mohammad Ali; Muradkhanli, Leyla; Weshah, Hadeel Abdullah; Hamdan, Hala; Abuhashish, Mutaz Mohammed (Research Parks Publishing LLC, 2024)
This study explores the theoretical foundations of artificial intelligence (AI) and big data, focusing on their role in the Fourth Industrial Revolution and sustainable development. Despite growing recognition of big data’s transformative potential, there is limited understanding of its specific impact on decision-making and societal transformation towards achieving sustainable development goals (SDGs). The research aims to fill this gap by analyzing how big data can support e-government initiatives and development objectives. Using a descriptive and analytical methodology, including a case study approach, the study examines the primary techniques and projects that facilitate large-scale data analysis in digital transformation. Results reveal that big data plays a critical role in monitoring progress, informing decisions, and driving social change aligned with SDGs. These findings contribute to a better understanding of big data’s value in modern governance and sustainable development efforts.